Patient perceptions of living with head and neck lymphoedema and the impacts to swallowing, voice and speech function. (25th July 2018) - Jeans, Claire; Ward, Elizabeth C.; Cartmill, Bena; Vertigan, Anne E.; Pigott, Amanda E.; Nixon, Jodie L.; Wratten, Chris
Abstract: Head and neck lymphoedema (HNL) is common following head and neck cancer (HNC) treatment, and may contribute to numerous physical, functional and psychological symptoms. However, its impact on swallowing, voice and speech is less well understood. The aim of this study was to use interpretive description to explore patient perceptions relating to the impact of HNL on swallowing, voice and speech. Twelve participants, >3 months post HNC treatment and experiencing some form of HNL, participated in individual, semi‐structured interviews. Transcribed interviews underwent thematic analysis using an inductive approach, with subsequent member checking. Most participants felt their HNL impacted their swallowing and some had impacts on speech; although the impact on voice was less clear. Four themes emerged, including three themes relating to HNL and its impact on swallowing and speech: "it feels tight;" "it changes throughout the day;" "it requires daily self‐monitoring and management;" and a fourth general theme "it affects me in other ways." Participants perceived direct impacts from HNL to swallowing and speech. They often experienced daily symptom fluctuations that required additional strategies during times of increased difficulty. Findings highlight the need to improve patient education regarding the functional impacts of HNL and the importance of self‐management.